2016
DOI: 10.1080/14740338.2016.1195368
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of anti-diabetes drugs

Abstract: Introduction Cardiovascular disease remains the major contributor to morbidity and mortality in diabetes. From the need to reduce cardiovascular risk in diabetes and to ensure that such risk is not exacerbated by drug treatments, governmental regulators and drug manufacturers have focused on clinical trials evaluating cardiovascular outcomes. Areas covered Findings from mechanistic and clinical trials of biguanides, sulfonylureas, thiazolidinediones, dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 177 publications
0
8
0
Order By: Relevance
“…A growing number of studies have illustrated that SGLT2 inhibitors reduce the CV risk factors in T2DM and demonstrated that the function of attenuating cardiovascular dysfunction was not a significant contributor to the metabolic effects [ 11 , 24 , 25 ]. Ipragliflozin improved hyperglycemia, ameliorated the impaired p-AKT and p-eNOS, and prevented the development of endothelial dysfunction in STZ-induced diabetes mice, at least partially by attenuation of oxidative stress [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have illustrated that SGLT2 inhibitors reduce the CV risk factors in T2DM and demonstrated that the function of attenuating cardiovascular dysfunction was not a significant contributor to the metabolic effects [ 11 , 24 , 25 ]. Ipragliflozin improved hyperglycemia, ameliorated the impaired p-AKT and p-eNOS, and prevented the development of endothelial dysfunction in STZ-induced diabetes mice, at least partially by attenuation of oxidative stress [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have convincingly shown that SGLT2 inhibitors not only lower the A1C levels in diabetic individuals with an overall improvement in cardiovascular function, but also induce the development of renal and peripheral insulin sensitivity and β cell function, which means that the presence of SGLT2 inhibitors is of functional significance [ 10 ]. More importantly, studies have shown a beneficial decline in several other CV risk factors, cardiovascular morbidity, and mortality, and even all-cause death by using of SGLT2 inhibitors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have proposed the underlying mechanisms for the cardio-protective activity of various antidiabetes drug classes, there still exists few lacunae [4]. Improved CV outcomes with metformin were reported in patients with T2DM, which could be due to the improved endothelium-independent blood flow and enhancement of nitric oxide dependent or independent vasodilation [26]. The cardiac protective effects of the GLP-1 agonists is due to their renal protection, reduction in ischaemic injury, chronic inflammation and ectopic fat deposition [27,28].…”
Section: Mechanisms Of Action Of Antidiabetes Drugs On Cardiovascularmentioning
confidence: 99%
“…This is supported by 77% of survey respondents in the second survey round. Yet first-line treatment approaches have traditionally relied on the evidence of therapeutic strategies for the control of hyperglycemia [69], with little understanding on the effects of these treatments on cardiovascular risk [70].…”
Section: Prevention Of Cvd Among People Living With Diabetesmentioning
confidence: 99%